Morphogenèse, climat et sociétés dans la plaine de Sfax (Tunisie) depuis le Pléistocène supérieur : l'exemple du bassin versant de l'oued Chaâl-Tarfaoui - Noômène Fehri; Jean-Louis Ballais; Michel Bonifay (Physio-Géo)
This paper is a synthesis of relations between morphogenetic activity, climatic changes and human societies from Upper Pleistocene up to now, using a chronological and geomorpho-historico-archaeological approach.In wadi Chaâl-Tarfaoui catchment, Upper Pleistocene formations are sandy with nodular calcretes very probably wind blown at the end of Würmian period by southward winds. During Holocene they were removed by runoff into two main alluvial formations. The older one is the low Holocene historic pre-roman (prehistoric ?) formation and the younger one is the very low Holocene historic post-roman formation. A third formation has been deposited by 1969 exceptional floods. It is thinner than the previous formations.